Liquiritin Ameliorates Streptozotocin-Induced Gestational Diabetes in Pregnant Rat Model by Inhibiting Inflammation and Oxidative Stress Responses - Xing, Jiejie; Wang, Fang; Wei, Junxiu; Cao, Chenyuan (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background: Gestational diabetes is a significant medical complication that can develop during pregnancy, characterized by impaired glucose tolerance. This condition poses risks to both the mother and the developing fetus. Effective management of gestational diabetes is crucial to mitigate the potential complications. The current work was aimed at studying the therapeutic roles of the liquiritin on Streptozotocin (STZ)-induced gestational diabetes in pregnant rat models. Materials and Methods: The experimental rats with established pregnancies were administered 45 mg/kg of STZ to induce gestational diabetes, followed by an 18-day treatment with liquiritin. After the conclusion of treatments, the changes in body weight, fetal and placental weight, glucose, and insulin levels were evaluated. The concentrations of oxidative stress markers, antioxidants, and inflammatory cytokines in the liver tissues were evaluated using kits. The histological analysis was conducted on both liver and pancreas obtained from the experimental rats. Results: The findings of this work indicated that liquiritin at 10, 25, and 50 mg/kg dosages significantly elevated body weight, Hb, and insulin levels, and decreased placental weight, glucose, and HbA1c levels in the gestational diabetes rats. The liquiritin treatment effectively diminished oxidative stress markers, and inflammatory markers, and enhanced the antioxidants in the gestational diabetes rats. The histological analysis of the both liver and pancreas confirmed the beneficial characteristics of liquiritin. Conclusion: The findings of this work illustrate that liquiritin considerably mitigates gestational diabetes in pregnant rat models. Thus, it can be a viable therapy option for treating gestational diabetes in the future.
Keywords: Oxidative stress; Glycated hemoglobin; Placenta; Liquiritin; Insulin